Novel players in cardioprotection: Insulin like growth factor-1, angiotensin-(1–7) and angiotensin-(1–9). (November 2015) - Westermeier, Francisco; Bustamante, Mario; Pavez, Mario; García, Lorena; Chiong, Mario; Ocaranza, María Paz; Lavandero, Sergio
Graphical abstract: Abstract: Insulin-like growth factor-1, angiotensin-(1–7) and angiotensin-(1–9) have been proposed to be important mediators in cardioprotection. A large body of evidence indicates that insulin like growth factor-1 has pleotropic actions in the heart (i.e., contractility, metabolism, hypertrophy, autophagy, senescence and cell death) and, conversely, its deficiency is associated with impaired cardiac function. Recently, we reported that insulin like growth factor-1 receptor is also located in plasma membrane invaginations with perinuclear localization, highlighting the role of nuclear Ca 2+ signaling in the heart. In parallel, angiotensin-(1–7) and angiotensin (1–9) acting through Mas receptor and angiotensin type 2 receptor have emerged as a novel anti-hypertensive molecules promoting vasodilatation and preventing heart hypertrophy. In this review we discuss the scientific evidence available regarding insulin-like growth factor-1, angiotensin-(1–7) and angiotensin-(1–9) in cardioprotection and its potential application as novel therapeutic targets for treating cardiac diseases.